Dynamic Event-Triggered Path-Following Control of Underactuated Surface Vehicle With the Experiment Verification - Zhang, Guoqing; Liu, Shang; Huang, Jiangshuai; Zhang, Weidong (IEEE transactions on vehicular technology, 2022)
This paper investigated the dynamic event-triggered control scheme for the path-following activity of underactuated surface vehicle (USV) subject to actuator saturation and gain uncertainties. Specifically, a dynamic event-triggered mechanism with the adjustable threshold is developed to reduce the communication burden and the execution wear of actuators. Unlike most existing event-triggered results, in which the threshold parameters are always fixed, the developed mechanism can ensure that the triggering thresholds are updated online in an adaptive manner, so as to achieve better resource efficiency. Furthermore, taking the practical measurable variables (i.e., revolving speed of propeller and rudder angle) as the control input, an auxiliary system is designed to deal with the influence of actuator saturation, which is distinct from most existing saturation-tolerant methods for USV. For merits of the neural damping technique, both the internal and external uncertainties are remodeled and only four adaptive parameters require to be updated online. Considerable effort has been made to guarantee the semi-globally uniform ultimate bounded (SGUUB) stability. Finally, the numerical simulation and physical experiment are illustrated to demonstrate the remarkable performance of the proposed algorithm.